Implementasi Kurikulum Merdeka dalam Mewujudkan Profil Pelajar Pancasila Melalui Pendekatan Humanistik pada Pembelajaran Pendidikan Agama Islam - Afifah, Nur; Nursikin, Mukh (Fakultas Agama Islam Universitas Billfath, 2024)
The purpose of this study is to describe the implementation of an independent curriculum in realizing the profile of pancasila students through a humanistic approach to Islamic Education Learning. This method of research is qualitative with a descriptive qualitative approach, for data collection techniques using observation, interview, documentation methods. The data source in the study is divided into two, namely: primary data sources and secondary data sources. The results of the study that implementation of the Free Curriculum in realizing the profile of Pancasila students in the dimension of faith and fear and exaltedness through the Humanistic approach. Strategy Implementation of independent curriculum in realizing the profile of Pancasila students in the dimension of faith and fear of God YME and exalted in the Islamic junior Sudirman 2 Timur Salatiga, namely through exemplarity. Second through the Habit strategy and the following types of customs are culture 5 S: smile, say salam, solm, solm spanish and manners; readings of asmaul husna; daily prayer; morning apple; clean friday; healthy saturday. The third strategy is the Assistance Program, the first mentoring program in the form of an extraculicular program in forming religious characters in an effort to realize the profile of Pancasila students. Supporting Factors of the implementation of the independent curriculum in realizing the profile of the Pancasila student in the dimension of faith and fear of God YME and noble moral. The school inhibitor factor is on the outskirts of the city which is the entrance to the city so it has the socioeconomic characteristics of parents.